Promoting Economic Recovery From the Perspective of Energy-Economic Resilience: Model Construction and Case Study - Wang, Yueren; Gong, Zaijing; Pan, Wei (Frontiers in Energy Research, 2020)
Energy is both a basic resource needed for economic growth and an essential tool for economic recovery. The topic of resilience is becoming increasingly prominent in the energy-economic domain and has also entered policy discourse. Yet the measuring method of resilience based on post-disruption events and the relationship between energy consumption and economic recovery are far from settled. This paper develops the idea of resilience and proposes a model to evaluate the economic recovery ability of an economy from the perspective of energy consumption. It also proposes a decoupling model to address the impact of energy-related elements on economic recovery. These ideas are then used for a preliminary empirical analysis of 14 countries against the context of the 2007–2008 financial crisis. The analysis showed that developing countries generally performed better than developed countries, that energy consumption is not a necessity for promoting economic recovery, and that energy-economic decoupling has a positive effect on economic recovery.